Systematic Literature Review: Financial Performance on Financial Distress - Jenny Liana; Enggar Diah Puspa Arum (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to examine articles related to the effect of financial performance on financial distress. This study uses the Systematic Literature Review (SLR) method to identify, evaluate, and synthesize relevant empirical research results from reputable databases such as Scopus and Shinta. The literature search was conducted using a combination of the keywords “financial performance” and “financial distress.” Of the 171 articles identified, 20 articles met the inclusion criteria after undergoing a selection process using the PRISMA protocol, consisting of 13 articles from Scopus and 7 articles from Shinta. The results of this study indicate that financial performance affects financial distress. Several studies show various types of models/systems for predicting financial distress and other factors that influence financial distress. The results of this research can be expected to increase in-depth knowledge about the correlation between financial performance and financial distress, as well as provide useful insights for academics, regulators, and practitioners in managing corporate financial risk. By providing the best understanding of the components that influence financial distress, companies can take more proactive measures to maintain their financial stability and improve their overall operational performance.